Various aspects of bariatric surgery - a review - Jerzak, Aneta; Jakubowska, Katarzyna; Janocha, Aleksandra; Ziemba, Paweł (Journal of Education, Health and Sport, 2024)
Introduction and purpose Obesity is a complex, chronic disease that has recently reached epidemic proportions. According to the World Health Organization, the prevalence of this disease tripled since 1975, reaching 13% of the global population in 2016. A body mass index (BMI) > 30 kg/m² is typically the reference point for obesity in adults, and the mortality risk associated with obesity increases by 100% at BMI > 40 kg/ m² compared to individuals with normal body weight. The aim of the article is to present the benefits of bariatric surgery, encompassing not only weight loss but also a range of other advantages for obese patients undergoing the procedure. Materials and methods The literature included in the PubMed databases is searched through the words such as obesity, bariatric surgery. Description of the state of knowledge: The literature review shows the breadth of the issue. Obesity constitutes a public health crisis and a significant risk factor for many diseases, including cardiovascular diseases, diabetes, cancer, and numerous others. Since in most cases, lifestyle optimization and low-calorie diet alone are not sufficient, pharmacological interventions as well as surgical interventions are often necessary. Bariatric surgery remains the most effective treatment option, as it has been demonstrated to not only reduce body weight but also decrease mortality from cardiovascular diseases and extend overall life expectancy. Conclusions The benefits, complications, and selection of the best surgical method for treating obesity are still under investigation. However, research demonstrates the long-term effectiveness of bariatric surgery in weight loss and the remission of comorbidities such as type 2 diabetes, as well as in preventing obesity-related cancers.